2014
DOI: 10.1093/annonc/mdt533
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis on the diagnostic performance of FDG-PET/CT in detecting bone marrow involvement in newly diagnosed Hodgkin lymphoma: is bone marrow biopsy still necessary?

Abstract: Although the methodological quality of studies that were included in this systematic review and meta-analysis was moderate, the current evidence suggests that FDG-PET/CT may be an appropriate method to replace BMB in newly diagnosed Hodgkin lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 27 publications
4
70
0
4
Order By: Relevance
“…In previous studies, the same high diagnostic performance of 18 F-FDG PET/CT was observed, as described in a meta-analysis of 955 patients with sensitivity ranging from 87.5% to 100% (10). The sensitivity of PET for BMI was indeed suboptimal in our study (84%), and this finding, though not influential on treatment decision, should be taken into account during patient restaging in the case of resistant or relapsing lymphoma.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In previous studies, the same high diagnostic performance of 18 F-FDG PET/CT was observed, as described in a meta-analysis of 955 patients with sensitivity ranging from 87.5% to 100% (10). The sensitivity of PET for BMI was indeed suboptimal in our study (84%), and this finding, though not influential on treatment decision, should be taken into account during patient restaging in the case of resistant or relapsing lymphoma.…”
Section: Discussionsupporting
confidence: 85%
“…The sensitivity of PET for BMI was indeed suboptimal in our study (84%), and this finding, though not influential on treatment decision, should be taken into account during patient restaging in the case of resistant or relapsing lymphoma. When either a positive BMB or focal BM lesions on PET/CT that disappear during treatment in the following scans or both is considered as the standard reference for BMI by HL, as previously suggested (10,12), this is a more accurate method than BMB alone, because of the inability of BMB to detect BMI for the patchy nature of BM infiltration by HL. As a matter of fact, in our study only 12 of 180 patients (6.6%) had a positive BMB, whereas, predictably, most focal lesions recorded at baseline (86.8%) disappeared in the interim PET, in keeping with the negativization rate of interim PET in ABVD-treated HL (80%-85%) (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, a number of studies have shown the superiority of PET/CT over BMB in the evaluation of bone marrow involvement in the setting of Hodgkin Lymphoma (HL) in terms of diagnostic accuracy [8][9][10]. More recently, a number of studies have addressed this issue in the context of non-Hodgkin Lymphoma (NHL), particularly in diffuse large B-cell lymphoma (DLCL) with differing results [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A more extensive evaluation concerning the role of FDG PET/CT to assess bone marrow involvement in patients with newly diagnosed Hodgkin lymphoma was performed in a systematic review and metaanalysis by Adams et al [14]: despite different methodological aspects among the selected studies, pooled sensitivity and specificity of FDG PET/CT in assessing bone marrow involvement, with respect to BMB and follow FDG PET/CT scans used as reference standard, were 96.9% and 99.7%, respectively. Overall accuracy was 98.6%.…”
mentioning
confidence: 99%